Harnessing the Therapeutic Potential of Th17 Cells - Jonas Bystrom; Taher E. Taher; M. Sherwan Muhyaddin; Felix I. Clanchy; Pamela Mangat; Ali S. Jawad; Richard O. Williams; Rizgar A. Mageed (Mediators of Inflammation)
Th17 cells provide protective immunity to infections by fungi and extracellular bacteria as well as cancer but are also involved in chronic inflammation. The cells were first identified by their ability to produce interleukin 17A (IL-17A) and, subsequently, associated with chronic inflammation and autoimmunity. Th17 cells have some gene profile similarity with stem cells and can remain dormant in mucosal tissues for long periods. Indeed, recent studies suggest that functionally distinct subsets of pro- and anti-inflammatory Th17 cells can interchange phenotype and functions. For development, Th17 cells require activation of the transcription factors STAT3 and RORγt while RUNX1, c-Maf, and Aiolos are involved in changes of phenotype/functions. Attempts to harness Th17 cells against pathogens and cancer using vaccination strategies are being explored. The cells gain protective abilities when induced to produce interferon γ (IFNγ). In addition, treatment with antibodies to IL-17 is effective in treating patients with psoriasis, psoriatic arthritis, and refectory rheumatoid arthritis. Moreover, since RORγt is a nuclear receptor, it is likely to be a potential future drug target for modulating Th17 functions. This review explores pathways through which Th17 subsets are induced, the molecular basis of their plasticity, and potential therapeutic strategies for their modulation in diseases.